2016
DOI: 10.1007/978-3-319-41334-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine and Its Role in Chronic Diseases

Abstract: The use of natural products derived from plants as medicines precedes even the recorded human history. In the past few years there were renewed interests in developing natural compounds and understanding their target specificity for drug development for many devastating human diseases. This has been possible due to remarkable advancements in the development of sensitive chemistry and biology tools. Sanguinarine is a benzophenanthridine alkaloid derived from rhizomes of the plant species Sanguinaria canadensis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…Additionally, a few histone or DNA methylation inhibitors such as UNC0642 [41], UNC0224 [42], UNC1215 [43], and S-adenosylhomocysteine [44] were also found to have potential HDP-inducing activities (Table 1). Several natural products such as ikarugamycin [45, 46], cynaroside [47], and sanguinarine [48] that are known to have anti-inflammatory, antioxidative, and/or antimicrobial activities but with no confirmed epigenetic modification properties were also identified (Table 2). It is surprising to observe that a number of natural products appeared to inhibit HDP gene expression with a SSMD value of less than −3.0 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a few histone or DNA methylation inhibitors such as UNC0642 [41], UNC0224 [42], UNC1215 [43], and S-adenosylhomocysteine [44] were also found to have potential HDP-inducing activities (Table 1). Several natural products such as ikarugamycin [45, 46], cynaroside [47], and sanguinarine [48] that are known to have anti-inflammatory, antioxidative, and/or antimicrobial activities but with no confirmed epigenetic modification properties were also identified (Table 2). It is surprising to observe that a number of natural products appeared to inhibit HDP gene expression with a SSMD value of less than −3.0 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Sanguinarine is a benzophenanthridine alkaloid extracted from the bloodroot plant Sanguinaria canadensis known to have anti-inflammatory, antioxidative, antiproliferative, and proapoptotic properties [58]. Although its mechanisms of action remain unclear [48], sanguinarine was recently identified as a putative inhibitor of heat shock protein 90 (HSP90) [31], whose activity has been demonstrated to be regulated by reversible acetylation [59].…”
Section: Discussionmentioning
confidence: 99%
“…Natural herbal products or components are an important source of alternatives because of their low toxicity and low cost (Fu et al, 2018). One of the promising candidate is Sanguinarine Chloride (SC) (Mackraj et al, 2008;Basu and Kumar, 2016), a benzo phenanthridine alkaloid derived from the root of Sanguinaria Canadensis and other poppy-fumaria species, which has been proved to exert anti-tumor properties due to its anti-proliferation, antiangiogenic and anti-invasive properties in various preclinical studies (Gaziano et al, 2016;Achkar et al, 2017). Specifically, SC could inhibit angiogenesis of cancer cells via blocking VEGF-induced vessel growth, cell migration, sprouting, and survival (Galadari et al, 2017;Xu et al, 2012;Eun and Koh, 2004;Basini et al, 2007a;Basini et al, 2007c).…”
Section: Introductionmentioning
confidence: 99%
“…Other biological and pharmacological activities of sanguinarine include anti-inflammatory, antioxidant and antitumor. Recently, these activities have attracted greater attention from researchers around the world [ 13 ]. A study by Jeng reported that the effect of sanguinarine on platelet activation in vitro is related to the production of thromboxane and cAMP [ 14 ].…”
Section: Introductionmentioning
confidence: 99%